Identification of candidate regulators of mandibular bone loss in FcγRIIB -/- Mice - Nithidol Sakunrangsit (Nature Portfolio, 2021)
Abstract Patients with systemic lupus erythematosus (SLE) have increased inflammatory cytokines, leading to periodontitis and alveolar bone loss. However, the mechanisms driving this phenomenon are still unknown. Here, we have identified novel therapeutic targets for and mediators of lupus-mediated bone loss using RNA-sequencing (RNA-seq) in a FcγRIIB -/- mouse model of lupus associated osteopenia. A total of 2,710 upregulated and 3,252 downregulated DEGs were identified. The GO and KEGG annotations revealed that osteoclast differentiation, bone mineralization, ossification, and myeloid cell development were downregulated. WikiPathways indicated that Hedgehog, TNFα NF-κB and Notch signaling pathway were also decreased. We identified downregulated targets, Sufu and Serpina12, that have important roles in bone homeostasis. Sufu and Serpina12 were related to Hedgehog signaling proteins, including Gli1, Gli2, Gli3, Ptch1, and Ptch2. Gene knockdown analysis demonstrated that Sufu, and Serpina12 contributed to osteoclastogenesis and osteoblastogenesis, respectively. Osteoclast and osteoblast marker genes were significantly decreased in Sufu-deficient and Serpina12-deficient cells, respectively. Our results suggest that alterations in Hedgehog signaling play an important role in the pathogenesis of osteopenia in FcγRIIB -/- mice. The novel DEGs and pathways identified in this study provide new insight into the underlying mechanisms of mandibular bone loss during lupus development.